Audience Insights on Unhealthy F&B Advertisements via Cultivation Theory: A Visual Communication Study - Matussin , Muizzah; Valdez, Nena Padilla; Mumin, Mas Ayu (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
This research explores how visual communication tactics and regulatory policies in advertisements may affect the perceptions of young adults in Brunei Darussalam on unhealthy food and beverage consumption. Following the regulations employed since 2021, this present research investigates its implications towards the young adult population of ages 18 – 26 years old who are also majorly exposed to persuasive content. The study analyses the role of visual aspects and their elements in advertisements in grabbing attention, shaping consumption behaviour, and the success and failure of the current regulatory framework, and its potential challenges in the dynamic light of contemporary media settings. Through a qualitative research design, in-depth semi-structured interviews were carried out among the local young adults to grasp their understandings and perceptions towards advertising, lifestyle dietary routines, as well as their awareness and opinions towards the existing regulations. Cultivation Theory served as the study’s underlying theoretical framework to interpret how the process of long-term media exposure has the ability to play a role in consumers’ attitudes and norms. The findings indicate that, although the respondents understand the health consequences of unhealthy food, visually appealing advertisements, especially those seen rapidly on digital platforms, continue to significantly contribute to their cravings and mindless dietary habits. Furthermore, the policies and regulations currently in place were viewed as insufficient as they did not have enough coverage in areas where permissive contents are still disseminated in digital spaces. With that concern in mind, a comparison with various reform proposals and guidelines published by international organisations, such as WHO and UNICEF, is considered to align with where the compliance and standards are not met.